2010
DOI: 10.1111/j.1468-2478.2010.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

From Global Village to Virtual Battlespace: The Colonizing of the Internet and the Extension of Realpolitik

Abstract: From the earliest years of the Internet's creation, cyberspace has been distinguished from other types of political space because of three unique qualities: (i) its ability to mobilize users, particularly ''outsiders'' including those who have not been easily included in political systems using conventional means; (ii) its ability to quickly provide large quantities of information of uncertain or unregulated quality; and (iii) its ability to shrink distances between users, in some sense rendering conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 33 publications
0
23
0
4
Order By: Relevance
“…However, "the platforms were not designed to cater to activist users" (Youmans & York, 2012, p. 317): On one hand, governance of social media is driven by commercial considerations, and the platforms' rules and architectures may constrain political engagement (Youmans & York, 2012, p. 317). On the other hand, no cyberspace has remained simply an exterritorial "global village" for freedom seekers, but the internet has always been subject to the extension of realpolitik, 1 namely an extension of the battlespace and an extension of the marketplace (Manjikian, 2010). Both aspects have a significant impact on the practice of using Arab social media.…”
Section: The Arab Social Media Between a Free Space And Realpolitikmentioning
confidence: 99%
“…However, "the platforms were not designed to cater to activist users" (Youmans & York, 2012, p. 317): On one hand, governance of social media is driven by commercial considerations, and the platforms' rules and architectures may constrain political engagement (Youmans & York, 2012, p. 317). On the other hand, no cyberspace has remained simply an exterritorial "global village" for freedom seekers, but the internet has always been subject to the extension of realpolitik, 1 namely an extension of the battlespace and an extension of the marketplace (Manjikian, 2010). Both aspects have a significant impact on the practice of using Arab social media.…”
Section: The Arab Social Media Between a Free Space And Realpolitikmentioning
confidence: 99%
“…Studies that explore forms of "cyber citizenship" have shown that the Internet is used for nation-building and reinforces national identity (Manjikian, 2010). A nation with an active cybercitizenship encourages the general population of citizens to take greater responsibility to ensure cybersecurity (Harknett & Stever, 2009).…”
Section: Active Cybercitizenrymentioning
confidence: 99%
“…Developed and developing countries alike have harnessed the power of ICT to spur economic development via e-commerce, and cyberspace has joined land, sea, air, and space as a potential arena for warfare and international conflict (Gorman & Barnes, 2011;Manjikian, 2010). The possibilities and risks inherent in the dissemination of ICT necessitate implementation of cybersecurity initiatives (Brechbühl, Bruce, Dynes, & Johnson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Visto que muitas das concepções da disciplina foram cunhadas dentro de um parâmetro realista, durante o século XX, que via no "sistema internacional" o Estado enquanto seu ator principal, separando a "política nacional" da "política internacional", tais concepções n~o se coadunam com a realidade do ciberespaço (Choucri e Goldsmith, 2012;Choucri, 2012;Manjikian, 2010) marcado por questões, para citar apenas alguns exemplos, como a multiplicidade de atores e suas influências numa dinâmica de difusão do poder (Nye Jr, 2010; delimitações territoriais fluídas que implicam numa movimentação também fluída da informação (Fernandes, 2012;Martins, 2012); interpenetração de sistemas de controle de operação civis e militares (Greathouse, 2014); e o problema da anonimidade que resulta em dificuldades de atribuição em contextos de ataques cibernéticos (Chawki, 2006;Shaheen, 2014;Kiggins, 2014).…”
Section: A "Ciberização" Das Relações Internacionaisunclassified